Influence of plasma-enhanced combustion on RBCC engine using URANS - Wei-Rui Zhang; Yuan-Shu Liu; Xiang-Rui Zou; Chaoqi Xu; Rui Xue (Scientific Reports)
Abstract The rocket-based combined-cycle (RBCC) engine is regarded as one of the most viable propulsion systems for single-stage-to-orbit launch vehicles. Because of the relatively low total temperature of the incoming flow, it is difficult to maintain sustained and efficient subsonic combustion when the rocket engine is turned off. Mode transition and its control have also become critical techniques in the RBCC study. In the current work, it is proposed for the first time to improve the performance of RBCC engines in mode transition by using plasma combustion support. The numerical simulation and validation were conducted on the full path configuration of the RBCC engine, which is suitable for wide range operation. The impact of multi-channel gliding arc (MCGA) plasma-assisted combustion technology on the flow field was investigated during the transition phases from RBCC ejector/ramjet mode to ramjet/scramjet mode. The results show that: Adding arc plasma into the cavities at low Mach numbers promotes the heat release of the fuel, expanding the high-temperature flame range in the combustor. Although it weakens the ability of some air inlet to capture air, it overall increases engine thrust and diminishes aerodynamic drag during the transition process from ejector/ramjet mode. At high Mach numbers, the fast incoming flow speed results in the inability of the fuel to mix and burn with air in a timely manner, resulting in poor heat release and work performance. However, the addition of arc plasma for combustion support using the same mode transition method reduces the thrust fluctuation of the RBCC engine during the ramjet/scramjet mode transition process, greatly reducing the time required for mode transition, reducing engine resistance, and significantly improving engine thrust.